Early Growth of Indigofera zollingeriana Mutant 2 Seedlings Under Various Gamma Ray Doses and Salinity Stress - Nadir, Marhamah; Rinduwati; Mas’ud, Emban Ibnurusyd; Syamsia; Kadir, Muhammad; Pertiwi, Suci; Putri, Rezkita; Asmiati; Sudirman, Witri Maulani (Faculty of Animal Science, Universitas Brawijaya, 2025)
The utilization of saline land for Indigofera zollingeriana cultivation is an opportunity to develop livestock in coastal areas. Salinity in coastal areas influences plant growth, particularly in the initial growth stages, because high salinity levels inhibit the uptake of both water and nutrients from the roots so that the plants will dry out. The objectives of this study were to evaluate the effects of various doses of gamma irradiation and NaCl stress on the early growth of Indigofera zollingeriana Mutant-2 seeds via a complete randomized design (CRD) with a 2x5 factorial pattern with 3 replications. The factors were salinity stress and irradiation dose. The first factor was salinity stress, which consisted of 0 mM NaCl and 40 mM NaCl. Second, the irradiation doses were 0 Gy, 50 Gy, 100 Gy, 150 Gy, and 200 Gy. The research results were analysed via analysis of variance (ANOVA), and significantly different treatments were evaluated via the DMRT test via the SAS Studio program. There was a significant difference in the effects of irradiation dose and NaCl stress on the germination rate, germination rate, mortality rate, radicle length, and plumula length, but the results were not significant for the seedling height, stem diameter, root length, number of cotyledons, or number of leaves. The DMRT results revealed that Indigofera treated with irradiation at a dose of 200 Gy had better germination rates, mortality rates, radicle rates, and plumula rates under both salinity stress conditions and gamma ray doses.